Staging autos-de-fe: Sense and Sacramentality during the Spanish Reformation - Phipps, Kathryn (Renaissance and Reformation / Renaissance et Réforme, 2025)
The Spanish Inquisition’s notorious public executions, celebrated in tandem with elaborate spectacles called autos-de-fe, foreground the contested theological weight of death and the senses at the apogee of the Spanish Reformation. Joining efforts to re-evaluate the sensory in early modernity, this article argues that contemporaneous accounts of autos-de-fe simultaneously perpetuate and challenge the notion that the Reformation constituted a fundamental change to theological interpretations of the senses. Published evangelical treatises by Reinaldo González de Montes and Juan Pérez de Pineda, alongside official manuscripts stored in the Inquisition’s archives, collectively elucidate the transformations of the senses in the aftermath of the Reformation in Spain. Moreover, Pérez’s corpus exemplifies Protestantism’s paradoxical interpretations of the deadly autos, viewing their sensorial abundance at once as profoundly significant and utterly meaningless.